Exploring EFL Teachers’ Understandings of Language Learning Psychology - Sureepong Phothongsunan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
Despite having become a key field in applied linguistics, language learning psychology (LLP) research is found to emphasize more on learners rather than teachers. 30 EFL teachers reported on their understandings on LLP within the EFL contexts in this study. How the teachers working in three different schools in Thailand conceptualize and apply five LLP constructs, namely 1) motivation, 2) willingness to communicate, 3) emotion, 4) self-concept, and 5) group dynamics in their classrooms were explored with a mixed-methods design including a survey and interviews. Descriptive statistics and Pearson correlation analyses were undertaken to find out any relationships among these five LLP constructs, whereas qualitative findings were investigated thematically. It was found that motivation, willingness to communicate, and emotion appeared vital in the teachers’ classroom experiences. The teachers also described their role in creating the emotional side of the classroom and in creating a supportive and positive learning environment. The findings shed light on teacher psychology and professional wellness and the role of teaching practices that take into account emotional responses.